Testing alternative hypotheses on the origin and speciation of Hawaiian katydids - Rakesh, Mohan; Aris-Brosou, Stephane; Xia, Xuhua (Université d'Ottawa | University of Ottawa, 2022)
BACKGROUND: Hawaiian Islands offer a unique and dynamic evolutionary theatre for studying origin and speciation as the islands themselves sequentially formed by erupting undersea volcanos, which would subsequently become dormant and extinct. Such dynamics have not been used to resolve the controversy surrounding the origin and speciation of Hawaiian katydids in the genus Banza, whose ancestor could be from either the Old-World genera Ruspolia and Euconocephalus, or the New World Neoconocephalus. To address this question, we performed a chronophylogeographic analysis of Banza species together with close relatives from the Old and New Worlds. RESULTS: Based on extensive dated phylogeographic analyses of two mitochondrial genes (COX1 and CYTB), we show that our data are consistent with the interpretation that extant Banza species resulted from two colonization events, both by katydids from the Old World rather than from the New World. The first event was by an ancestral lineage of Euconocephalus about 6 million years ago (mya) after the formation of Nihoa about 7.3 mya, giving rise to B. nihoa. The second colonization event was by a sister lineage of Ruspolia dubia. The dating result suggests that this ancestral lineage first colonized an older island in the Hawaiian-Emperor seamount chain before the emergence of Hawaii Islands, but colonized Kauai after its emergence in 5.8 mya. This second colonization gave rise to the rest of the Banza species in two major lineages, one on the older northwestern islands, and the other on the newer southwestern islands. CONCLUSION: Chronophylogeographic analyses with well-sampled taxa proved crucial for resolving phylogeographic controversies on the origin and evolution of species colonizing a new environment.
Keywords: Phylogeography; Biogeography; Geophylogeny; Speciation; Phylogenetics; DNA barcoding; Hawaii Islands